Pergeseran Ujaran dari Kritik menuju Ujaran Kebencian dalam Konflik Digital Iran-Amerika Serikat-Israel: Kajian Pragmasemantik (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to examine the shift of utterances from criticism to hate speech in digital communication related to the Iran-United States-Israel conflict in 2026 on social media. The study focuses on the transformation of the functions and meanings of users’ comments, which initially appear as opinions or criticism but gradually evolve into expressions that contain elements of hate speech. This research employed a descriptive qualitative method, using a pragmalinguistic approach to interpret the meanings of utterances based on linguistic context, speaker intention, and surrounding social circumstances. The data were obtained from users’ comments on posts shared on Instagram and TikTok through observation and documentation. The collected data were then analyzed by classifying utterances into several categories, including criticism, emotional criticism, offensive speech, personal attack, and hate speech. The findings reveal that the transformation of utterances into hate speech occurs gradually rather than instantly. Initially, evaluative criticism tends to shift due to the increasing use of emotional, sarcastic, and derogatory language, eventually developing into personal attacks, negative labeling, and even dehumanization toward certain groups. These findings indicate that social media may amplify the emergence of hate speech by providing users with broader opportunities to express emotions freely. Therefore, the pragmasemantic approach is considered relevant in understanding the dynamics of meaning transformation in digital communication.